Utilization of and barriers to enhanced recovery pathway implementation in pediatric urology. Issue 3 (June 2021) - Chan, Yvonne Y.; Rosoklija, Ilina; Meade, Patrick; Burjek, Nicholas E.; Raval, Mehul V.; Yerkes, Elizabeth B.; Rove, Kyle O.; Chu, David I.
Summary: Introduction: Enhanced Recovery Pathways (ERPs), also known as ERAS® pathways, are standardized pathways composed of 21–24 perioperative elements designed to improve post-surgical recovery. ERP has been shown to be safe and effective in children undergoing bladder reconstruction but has not been widely utilized. Objective: The aim of this study was to assess utilization of ERPs in pediatric urology and identify barriers to establishing these standardized pathways. Study design: Pediatric urologists who were members of the Societies for Pediatric Urology (SPU) were surveyed regarding their familiarity with standardized ERPs, current use of ERP elements, and encountered or perceived barriers to standardized ERP implementation. Willingness to implement ERP elements in a child undergoing bladder reconstruction was assessed with a 5-point Likert scale. Descriptive analysis was performed; Fisher's exact test was performed to assess associations between respondent demographics and ERP familiarity. Results: Of 714 distributed surveys, 113 (16%) valid responses were collected. 69% of respondents were male, 58% practiced at academic institutions, and 57% performed 1–5 bladder reconstructions a year. 61% were somewhat familiar or not familiar with standardized ERP. While 54% currently utilize individual ERP elements, only 20% have standardized pathways. Out of 24 possible ERP elements, a median of 15 elements (range 0–24) were implemented by the respondents whether they reported they were implementing ERP elements or had standardized pathways in place. 15 of 24 ERP elements were found to be nearly universally acceptable, with greater than 90% of respondents being somewhat or very willing to implement them in the presented case scenario (Summary Figure). 62% and 56% of those who currently implement ERP elements and experienced barriers noted lack of administrative/leadership support and inability to achieve consensus among pediatric colleagues, respectively, as common barriers in standardization. For those who have not attempted standardization, the most common perceived barrier was pathway unfamiliarity (48%). Discussion: Over half of respondents were not familiar with enhanced recovery pathways but were willing to implement a majority of the pathway elements, suggesting potential for ERP standardization in pediatric urology. Buy-in from colleagues and leadership would be necessary to overcome perceived barriers of standardized pathway development. Conclusion: Administrative support and more widespread knowledge of ERP amongst pediatric urologists are necessary to facilitate further implementation in children undergoing bladder reconstruction. Summary Figure Summary Figure